A dozen years of ovarian tissue cryopreservation at a pediatric hospital: tracking program and patient metrics while adapting to increasing needs - Kathryn L. McElhinney, M.D; Tara Kennedy, B.S; Erin E. Rowell, M.D; Monica M. Laronda, Ph.D (Elsevier, 2024)
Objective: To review the program and patient metrics for ovarian tissue cryopreservation (OTC) within a comprehensive pediatric fertility preservation program in its first 12 years of development. Design: Retrospective review. Setting: A tertiary children's hospital in a large urban center between March 2011 and February 2023. Patients: Pediatric patients who underwent OTC. Interventions: Unilateral oophorectomy for OTC. Main Outcome Measures: Patient demographics and clinical course information were collected for analysis. Results: A total of 184 patients underwent OTC in the first 12 years. One hundred fifteen patients were prepubertal at the time of OTC, and 69 were postpubertal. In total, 128 patients (69.6%) received part of their planned therapy before OTC. Starting in 2018, 104 participants (92.0%) donated tissue to research, 99 participants (87.6%) donated blood, and 102 (90.2%) donated media to research. There was a decrease in the median age of patients who underwent OTC from 16.4-6.6 years and an overall increase in the proportion of patients per year that were prepubertal. Forty-eight (26.0%) patients who underwent OTC were outside referrals and traveled from as far as Seattle, Washington. Conclusion: During the first 12 years of this program, oncofertility research increased, annual tissue cryopreservation cases increased, and the median age of those who underwent OTC decreased. The program was adapted to build a stand-alone gonadal tissue processing suite and specialized in prepubertal ovarian tissue processing. The program will continue to adapt to patient needs in the upcoming decades because restoration technologies advance through research supported by this and collaborating programs.